Midface prosthetic rehabilitation. Issue 2 (April 2016) - Vander Poorten, Vincent; Meulemans, Jeroen; Delaere, Pierre
Abstract : Purpose of review: Midfacial defects resulting from head and neck oncological resections can be addressed by microvascular reconstructive techniques using autologous tissue. In specific indications, however, prosthetic rehabilitation can give a superior aesthetic outcome, combined with a less intensive surgical strain on the patient. In other situations, the combination of both approaches can restore much extended defects satisfactorily. This review lists the indications, technical prerequisites for success, and outcome of midface prosthetic rehabilitation. Recent findings: With increasing numbers of patients treated, the optimal treatment protocol has become clear, and is now validated by long-term results in accumulating patient numbers. Modern three-dimensional planning techniques and three-dimensional printing of drill-guides, custom-made implants, abutments and epitheses further increase the predictability of success and the aesthetic outcome. Summary: Midface prosthetic rehabilitation nowadays has a definite place in the armamentarium of the head and neck oncologic surgeon and is invaluable in restoring quality of life and social functioning of patients with extensive midfacial defects following oncological resections.